1995
DOI: 10.1016/0014-5793(94)01452-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subcellular and zonal distribution of glucokinase in rat liver during postnatal development

Abstract: Subcellular and zonal distribution of glucokinase in rat liver during postnatal development was examined immunohistocbemicaily. Before day 11 after birth, only some hepatocytes were immunostained, and a positive immunostaining was found in the cytoplasm but not in the nucleus. No zonal distribution of glucokinase was observed in livers of such pups. From day 15, at which time a dietary change from milk to laboratory chow begins to take place, glucokinase immunoreactivity increased; this increase was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…4 (which maps GK activity on a point-by point basis along the lobular radius), that in control livers the immediate perivenous cells contained a large concentration of GK (substantially greater than in the immediate periportal cells, and much greater than in the cells of the midzone of the lobule where the activity of GK is in any case probably overestimated due to difficulty of curve-fitting to the abrupt changes in this region). This distribution has similarities with that shown by immunochemical methods to be established by 30 d after birth in normal rats (19). In control livers, there are ‫ف‬ 15 hepatocytes along the lobular radius.…”
Section: Hepatic Glucose Production In Nondigitonized Perfused Liverssupporting
confidence: 78%
“…4 (which maps GK activity on a point-by point basis along the lobular radius), that in control livers the immediate perivenous cells contained a large concentration of GK (substantially greater than in the immediate periportal cells, and much greater than in the cells of the midzone of the lobule where the activity of GK is in any case probably overestimated due to difficulty of curve-fitting to the abrupt changes in this region). This distribution has similarities with that shown by immunochemical methods to be established by 30 d after birth in normal rats (19). In control livers, there are ‫ف‬ 15 hepatocytes along the lobular radius.…”
Section: Hepatic Glucose Production In Nondigitonized Perfused Liverssupporting
confidence: 78%
“…GK and GKRP are not expressed homogenously in all the parenchymal cells in the liver. GK is expressed from periportal to perivenous areas in an increasing gradient in normal (38,61) and ZDF rats (data not shown). Even in perivenous areas, the intensities of immunofluorescence of GK and GKRP vary among hepatocytes (data not shown).…”
Section: Methodsmentioning
confidence: 91%
“…Studies using cultured hepatocytes have repeatedly shown that glucose per se is a potent stimulator of GK translocation (2,13,60,62), whereas the results regarding the effect of insulin are controversial (3,13,61). We recently reported (15) that increases in plasma glucose and/or insulin levels within the physiological range cause rapid GK translocation in conscious normal rats.…”
mentioning
confidence: 99%
“…After incubation, the beads were washed five times with binding buffer (10-fold volume of beads) and resuspended in elution buffer (binding buffer containing 10 mM reduced glutathione). The bound proteins were resolved by 10% SDS-PAGE and visualized by Western blotting with rabbit anti-glucokinase antibody or anti-p␤PCCase serum as described previously (13,20).…”
Section: Preparation Of Rat Pancreatic Islet and Livermentioning
confidence: 99%
“…After incubation, the beads were washed five times with binding buffer (10-fold volume of beads) and resuspended in elution buffer (binding buffer containing 10 mM reduced glutathione). The bound proteins were resolved by 10% SDS-PAGE and visualized by Western blotting with rabbit anti-glucokinase antibody or anti-p␤PCCase serum as described previously (13,20).Assay for Glucokinase Activity-Glucokinase enzyme activity was measured by a fluorometric assay according to the method reported previously (21). Glucokinase activity was measured as the fluorescence of NADPH at excitation and emission wavelengths of 340 and 450 nm, respectively.…”
mentioning
confidence: 99%